Does CAD Smell Like Code? A Mapping Between Violation of Object Oriented Programming Design Principles and Computer Aided Design Modelling. (May 2022) - Rosso, P.; Gopsill, J.; Burgess, S. C.; Hicks, B.
Abstract: In objected-oriented design, "smells" are symptoms of code violating design principles. When a deadline is looming, decisions can affect the long-term quality of a code or CAD. Given this and the similarities between object-oriented code and CAD models, this paper introduces a set of CAD smells. These smells are derived from a top-down review of potential CAD smells mapped against the reported code smells that violate abstraction, modularity, encapsulation, and hierarchy principles. This list was further reviewed considering CAD systems and specific examples (some illustrated in the paper).